Electrical stimulation of human corticospinal axons at the level of the lumbar spinal segments. (16th January 2019) - Škarabot, Jakob; Ansdell, Paul; Brownstein, Callum G.; Thomas, Kevin; Howatson, Glyn; Goodall, Stuart; Durbaba, Rade
Abstract: Electrical stimulation over the mastoids or thoracic spinous processes has been used to assess subcortical contribution to corticospinal excitability, but responses are difficult to evoke in the resting lower limbs or are limited to only a few muscle groups. This might be mitigated by delivering the stimuli lower on the spinal column, where the descending tracts contain a greater relative density of motoneurons projecting to lower limb muscles. We investigated activation of the corticospinal axons innervating tibialis anterior (TA) and rectus femoris (RF) by applying a single electrical stimulus over the first lumbar spinous process (LS). LS was paired with transcranial magnetic stimulation (TMS) at interstimulus intervals (ISIs) of −16 (TMS before LS) to 14 ms (LS before TMS). The relationship between muscle contraction strength (10%–100% maximal) and the amplitude of single‐pulse TMS and LS responses was also investigated. Compared to the responses to TMS alone, responses to paired stimulation were significantly occluded in both muscles for ISIs ≥−8 ms ( p  ≤ 0.035), consistent with collision of descending volleys from TMS with antidromic volleys originating from LS. This suggests that TMS and LS activate some of the same corticospinal axons. Additionally, the amplitude of TMS and LS responses increased with increasing contraction strengths with no change in onset latency, suggesting responses to LS are evoked transsynaptically and have a monosynaptic component. Taken together, these experiments provide evidence that LS is an alternative method that could be used to discern segmental changes in the corticospinal tract when targeting lower limb muscles. Abstract : Electrical stimulation over the first lumbar spinous process (LS) delivered prior to transcranial magnetic stimulation (TMS), resulted in the occlusion of TMS evoked responses. When LS and TMS were delivered individually, respective responses showed similar increasing behaviour in relation to increasing contraction strength. These results suggest that LS activates some of the same corticospinal axons as TMS and can be used to assess the subcortical contribution to the corticospinal response.